Spatial and Short-Term Temporal Patterns of Octocoral Assemblages in the West Philippine Sea - Lalas, Jue Alef A.; Lim, Romina Therese S.; Cabasan, Joey P.; Segumalian, Christine S.; Luciano, Rhea Mae A.; Valino, Darryl Anthony M.; Jacinto, Melchor R.; Arceo, Hazel O.; Baria-Rodriguez, Maria Vanessa (Frontiers in Marine Science, 2022)
Octocorals are relatively understudied than other coral reef organisms despite their ecological and economic values. The Philippines is known to have high marine biodiversity, but information on octocorals is lacking. This study investigated spatial and temporal variations in the assemblage of octocorals in selected reef sites in the West Philippine Sea (WPS)- the Kalayaan Island Group (i.e., Pag-asa, Sabina, Lawak, and Northeast Investigator) and Ulugan in 2017 and 2019. Results showed high octocoral taxonomic richness (at least 10 families) in the study sites. Mean percent octocoral cover in WPS was 5.35% SE ± 0.55, with Sabina having the highest octocoral cover in both years. Significant differences in octocoral cover were observed among sites in both years, but among-station differences were only observed in 2017. Octocoral assemblage also differed among sites in both years (ANOSIM: R> 0.5, p <0.05), wherein different octocoral taxa dominated in different sites. In particular, variations were driven by high cover of holaxonians, nephtheids, and coelogorgiids in Sabina, and clavulariids, tubiporiids, and xeniids in Northeast Investigator in 2017. In 2019, significant variations were driven by high cover of helioporiids in Pag-asa, while Sabina had higher abundance of holaxonians, nephtheids, alcyoniids, and xeniids. Short-term temporal variation on octocoral cover in monitoring stations in Pag-asa was not observed (Kruskal-Wallis, p > 0.05), although the overall mean octocoral cover increased from 1.23% ± SE 0.47 in 2017 to 2.09% SE ± 0.37 in 2019. Further, there was no significant change in the octocoral assemblage in Pag-asa between years (ANOSIM, R = 0.11, p = 0.07). This study highlights high octocoral taxonomic richness in the WPS relative to other sites in the Indo-Pacific Region and provides baseline information on the octocoral assemblages, which can be useful for future ecological studies and marine biodiversity conservation efforts.